Предмет:
МатематикаАвтор:
анонимПрименим формулу:
(а - в) * (а + в) = а^2 - в^2;
(3х - 1) * (3х + 1) = 9х^2 - 1.
Применим формулу:
(а + в)^2 = а^2 + в^2 + 2ав;
(3х + 1)^2 = 9х^2 + 1 + 6х;
Подставим в наше выражение:
9х^2 - 1 + 9х^2 + 1 + 6х;
Приводим подобные:
18х^2 + 6х = 6х(3х + 1).
Ответ: 6х(3х + 1).
Автор:
adrienvelezДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть